(3efXheI aj eVGejf GdCNHGQ GdhGQOI aj BOGH GdeWGYe hGdeTGQH hefGaYgGs - (3GdCYSe, eMSf Hf eQJVi Hf bGSe, J (B1238 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B.. (3bGd GdfGXe HYO GdHSedI GdMeO ddg Udi GdHGQj Ydi GdfHj CMeO GdeNJGQ (B***(3hBdg GdCWgGQ CQHGH GdcQe hef Hge JeJ Ydi GdNdb GdfYe (B...s
(3BNQgG (B:s
.. (3dcf CJi ajgG MOjK Cf ef CMdgG Gdehdi abO WGH GddHf (B*** (3Ke dfUd PG GdebGe Ydi GdfHj GdeUWai hBds
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\22s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis